Three-Perspective Approach: Towards a New Configuration of the Photographic Archive - Colunge Rosales, Ángel Enrique (2024)
The article proposes a new methodology, the three-perspective approach, for the classification of photographs in archives. It is based on the intersection of visual economy and mass communication theory. This approach understands the archive as a relational phenomenon, where images participate in networks of meaning and power. The three perspectives are the sender and production, the image and circulation, and the audience and consumption, all framed within a specific space/time. The methodology is applied to the case study of the TAFOS project collection, active between 1986 and 1998. The approach allows for multiple classifications according to the version of the archive, and opens new ways to explore its communicative and expressive potential. The proposal seeks to strengthen the continuity of photographic archives as living agents decentered from library logic, promoting discursive diversity and resisting totalitarianism that restricts their action and enunciation.